2018
DOI: 10.1016/j.physbeh.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A modified ketogenic gluten-free diet with MCT improves behavior in children with autism spectrum disorder

Abstract: Purpose The ketogenic diet is a low-carbohydrate, moderate protein, high-fat diet that has emerged as a potential treatment for autism spectrum disorder. Autism spectrum disorder is a neurodevelopmental disorder of social communication, and restricted, repetitive behaviors and interests in need of novel therapies. An open-label clinical trial was done in Honolulu, Hawaii to test a modified ketogenic diet for improvement of core clinical impairments in children with ASD. Intervention A modified ketogenic glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 47 publications
3
117
1
5
Order By: Relevance
“…Finally, some clinical studies have tested the feasibility of the ketogenic diet for the treatment of other neurological disorders. A clinical trial revealed that a modified version of the ketogenic diet improved core autism features in patients with autism spectrum disorder (Lee et al, 2018 ), and this was supported by animal studies (Ruskin et al, 2013 , 2017 ). In addition, pilot clinical studies reported that the MCT ketogenic diet improved the cognitive performance of patients with Alzheimer’s disease or mild cognitive impairment (Reger et al, 2004 ), and also reported that the ketogenic diet improved Parkinson’s disease symptoms (Vanitallie et al, 2005 ).…”
Section: Drug Development Based On the Ketogenic Dietmentioning
confidence: 95%
“…Finally, some clinical studies have tested the feasibility of the ketogenic diet for the treatment of other neurological disorders. A clinical trial revealed that a modified version of the ketogenic diet improved core autism features in patients with autism spectrum disorder (Lee et al, 2018 ), and this was supported by animal studies (Ruskin et al, 2013 , 2017 ). In addition, pilot clinical studies reported that the MCT ketogenic diet improved the cognitive performance of patients with Alzheimer’s disease or mild cognitive impairment (Reger et al, 2004 ), and also reported that the ketogenic diet improved Parkinson’s disease symptoms (Vanitallie et al, 2005 ).…”
Section: Drug Development Based On the Ketogenic Dietmentioning
confidence: 95%
“…Two non placebo-controlled studies were conducted (recruiting respectively 30 and 15 patients), both confirming the beneficial effects of KD in autistic patients. 96,97 Further studies are required to confirm these preliminary data and to analyze the possible impact of KD on autistic behavior.…”
Section: Ketogenic Diet (Kd)mentioning
confidence: 99%
“…The bacterial diversity and the abundance of Prevotella , Bifidobacterium , and Desulfovibrio taxa were found to be higher in ASD children with MTT treatment. The gastrointestinal disturbances and the alternation in the composition of the gut microbiota were restored or reversed by probiotics [ 123 , 124 ] and dietary [ 125 ] treatment in ASD children.…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%